On Critiques of "Stationarity is Dead: Whither Water Management?". Issue 9 (12th September 2015) - Milly, P. C. D.; Betancourt, Julio; Falkenmark, Malin; Hirsch, Robert M.; Kundzewicz, Zbigniew W.; Lettenmaier, Dennis P.; Stouffer, Ronald J.; Dettinger, Michael D.; Krysanova, Valentina
Abstract We review and comment upon some themes in the recent stream of critical commentary on the assertion that "stationarity is dead, " attempting to clear up some misunderstandings; to note points of agreement; to elaborate on matters in dispute; and to share further relevant thoughts.